Association between women's household decision-making autonomy and health insurance enrollment in sub-saharan Africa - Betregiorgis Zegeye; Dina Idriss-Wheeler; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Abdul-Aziz Seidu; Nicholas Kofi Adjei; Sanni Yaya (BMC, 2023)
Abstract Background Out of pocket payment for healthcare remains a barrier to accessing health care services in sub-Saharan Africa (SSA). Women's decision-making autonomy may be a strategy for healthcare access and utilization in the region. There is a dearth of evidence on the link between women's decision-making autonomy and health insurance enrollment. We, therefore, investigated the association between married women's household decision making autonomy and health insurance enrollment in SSA. Methods Demographic and Health Survey data of 29 countries in SSA conducted between 2010 and 2020 were analyzed. Both bivariate and multilevel logistic regression analyses were carried out to investigate the relationship between women's household decision-making autonomy and health insurance enrollment among married women. The results were presented as an adjusted odds ratio (AOR) and the 95% confidence interval (CI). Results The overall coverage of health insurance among married women was 21.3% (95% CI; 19.9-22.7%), with the highest and lowest coverage in Ghana (66.7%) and Burkina Faso (0.5%), respectively. The odds of health insurance enrollment was higher among women who had household decision-making autonomy (AOR = 1.33, 95% CI; 1.03-1.72) compared to women who had no household decision-making autonomy. Other covariates such as women's age, women's educational level, husband's educational level, wealth status, employment status, media exposure, and community socioeconomic status were found to be significantly associated with health insurance enrollment among married women. Conclusion Health insurance coverage is commonly low among married women in SSA. Women's household decision-making autonomy was found to be significantly associated with health insurance enrollment. Health-related policies to improve health insurance coverage should emphasize socioeconomic empowerment of married women in SSA.